O enunciado imagético e verbal no livro didático : uma análise discursiva - Souza, Parla Camila dos Reis de (2013)
Analyzing the incidence of images and mixed texts, in two editions of the textbook Português: linguagens of 1990 and 2010 for the third year of high school, we check the increase in these types of texts in the theoretical sections and in the exercises of this textbook. A more detailed comparison between editions showed a spread of images and mixed text approximately seven times more in the latest edition relative to the first. Given the occurrence of materialities imagistic and mixed, in the editions of the textbook Português: linguagens (2010), we investigated more two textbooks - Novas Palavras (2010) e Viva português: ensino médio (2010) making sure that an increase in the incidence of these types of texts can be understood as a tendency in these textbooks. From this, we analyze the representation, the relevance of these types of texts for teaching Portuguese language in high school proposed by these textbooks, mainly in the propositions of exercises made by these texts, noting few effective changes between editions of the textbook Português: linguagens in this effect. What can enhance this impasse between the highest incidence of these types of texts and their respective contributions to the teaching of Portuguese language is precisely the gap between the performances of the textbooks, which emphasize the need to work with the various languages, and their interiors, which demonstrate a relevance to verbal language, relegating to the low priority the mixed texts and the images. Indeed, these types of texts from our corpus have not acquired the importance compatible with the presentations discourses, because when they are used, quoted in the theoretical section and activities their materialities serve to decorate, illustrate, approximate the appearance of the textbook to the sites of Internet, since the referrals interpretatives of the exercises seldom consider their richness of meaning. However, when there is some consideration, the referrals tend to a more content-analysis of the constituent elements of each genre (cartoon, comic cartoon, advertisement etc.) in the exercise than making relations with other knowledge, for example. However, after 20 years (based on the two editions of the textbook Português: linguagens), the changes are backward, since very few times the syncretism of languages is worked. In this regard, we note that although the image and the mixed text are properly distributed on a large scale in the most textbooks that we studied, the materiality of these types of texts is not incorporated into the structure of the approach to teaching and learning of Portuguese Language proposed by the textbook to compete effectively as an element in the production of meaning. Trying to demonstrate how is the gap between the presentations and the use of the materiality of these types of texts inside the textbooks, we did a survey of the incidence of these texts and analyze four of them, based on Michel Foucault s theoretical postulates, notably his definition of utterance and archive, Discourse Analysis studies and the concept of discoursive memory postulated by JJ Courtine.